Integrated GWAS and mRNA Microarray Analysis Identified IFNG and CD40L as the Central Upstream Regulators in Primary Biliary Cholangitis. Issue 5 (15th March 2020) - Ueno, Kazuko; Aiba, Yoshihiro; Hitomi, Yuki; Shimoda, Shinji; Nakamura, Hitomi; Gervais, Olivier; Kawai, Yosuke; Kawashima, Minae; Nishida, Nao; Kohn, Seik‐Soon; Kojima, Kaname; Katsushima, Shinji; et al.
Abstract : Genome‐wide association studies (GWASs) in European and East Asian populations have identified more than 40 disease‐susceptibility genes in primary biliary cholangitis (PBC). The aim of this study is to computationally identify disease pathways, upstream regulators, and therapeutic targets in PBC through integrated GWAS and messenger RNA (mRNA) microarray analysis. Disease pathways and upstream regulators were analyzed with ingenuity pathway analysis in data set 1 for GWASs (1, 920 patients with PBC and 1, 770 controls), which included 261 annotated genes derived from 6, 760 single‐nucleotide polymorphisms ( P  < 0.00001), and data set 2 for mRNA microarray analysis of liver biopsy specimens (36 patients with PBC and 5 normal controls), which included 1, 574 genes with fold change >2 versus controls ( P  < 0.05). Hierarchical cluster analysis and categorization of cell type–specific genes were performed for data set 2. There were 27 genes, 10 pathways, and 149 upstream regulators that overlapped between data sets 1 and 2. All 10 pathways were immune‐related. The most significant common upstream regulators associated with PBC disease susceptibility identified were interferon‐gamma (IFNG) and CD40 ligand (CD40L). Hierarchical cluster analysis of data set 2 revealed two distinct groups of patients with PBC by disease activity. The most significant upstream regulators associated with disease activity were IFNG and CD40L. Several molecules expressed in B cells, T cells, Kupffer cells, and natural killer–like cells were identified as potential therapeutic targets in PBC with reference to a recently reported list of cell type–specific gene expression in the liver. Conclusion : Our integrated analysis using GWAS and mRNA microarray data sets predicted that IFNG and CD40L are the central upstream regulators in both disease susceptibility and activity of PBC and identified potential downstream therapeutic targets. Abstract :